Resilient balconies. Introducing water, energy, and food safety in multifamily housings - Valdivia Sisniegas, Richard H. (2022)
The urban density in cities is growing, which could favor land use efficiency, mobility and provides an opportunity for other environmental services; for those reasons is expected the increase of homes in high buildings in the coming decades. On the other hand, the urgency of initiatives for adaptation and mitigation to climate change in the cities has led to questions and rethinking for the built environment, as well as alternative proposals moved away from conventions.Considering the large number of families living in medium and high density multifamily homesin most of the world’s cities, the “resilient balconies” project proposes a change in the designand planning of the balcony space; destined to water, energy and food security to create anopportunity for survival face of the uncertain impacts of climate change on cities.